Safety and efficacy of electrical stimulation for lower-extremity muscle weakness in intensive care unit 2019 Novel Coronavirus patients: A phase I double-blinded randomized controlled trial - Zulbaran-Rojas, Alejandro; Mishra, Ramkinker; Rodriguez, Naima; Bara, Rasha O.; Lee, Myeounggon; Bagheri, Amir Behzad; Herlihy, James P.; Siddique, Muhammad; Najafi, Bijan (Frontiers in Medicine, 2022)
Background: Intensive care unit (ICU) prolonged immobilization may lead to lower-extremity muscle deconditioning among critically ill patients, particularly more accentuated in those with COVID-19 infection. Electrical stimulation (E-Stim) is known to improve musculoskeletal outcomes. This phase I double-blinded randomized controlled trial examined the safety and efficacy of lower-extremity E-Stim to prevent muscle deconditioning. Methods: Critically ill COVID-19 patients admitted to the ICU were randomly assigned to control (CG) or intervention (IG) groups. Both groups received daily E-Stim (1-hour) for up to 14 days on both gastrocnemius muscles (GNM). The device was functional in the IG and non-functional in the CG. Primary outcomes included ankle strength (Ankles) measured by an ankle-dynamometer, and GNM endurance (GNMe) in response to E-Stim assessed with surface-electromyography (sEMG). Outcomes were measured at baseline, 3 days, and 9 days. Results: Thirty-two (IG=16, CG=16) lower extremities in sixteen patients were independently assessed. The mean time between ICU admission and E-Stim therapy delivery was 1.8 ± 1.9 days (p = 0.29). At 3 days, the IG showed an improvement compared to the CG with medium effect sizes for Ankles (p = 0.06, Cohen’s d = 0.77) and GNMe (p = 0.06, d = 0.69). At 9 days, the IG GNMe was significantly higher than the CG (p = 0.04, d = 0.97) with a 6.3% improvement from baseline (p = 0.029). E-Stim did not alter vital signs (i.e., heart/respiratory rate, blood saturation of oxygen), showed no adverse events (i.e., pain, skin damage, discomfort), nor interfere with ICU standard of care procedures (i.e., mechanical ventilation, prone rotation). Conclusion: This study supports the safety and efficacy of early E-Stim therapy to potentially prevent deterioration of lower-extremity muscle conditions in critically ill COVID-19 patients recently admitted to the ICU. If confirmed in a larger sample, E-Stim may be used as a practical adjunctive therapy.